Structural Characterization of Factors for the Digital Training of Public Primary School Teachers: The Peruvian Case (LACCEI, 2024)
The aim of this study was to determine the key factors of the digital teacher training system in public primary schools, which aims to improve teachers’ digital competence. Digital competence is defined as the creative, critical, and safe use of Information and Communication Technologies (ICT). Worldwide, several countries use within their digital training programs institutional frameworks such as the European Framework for the Digital Competence of Educators, the International Society for Technology in Education (ISTE) and/or UNESCO. In Peru, the Framework for Good Teaching Performance, a guiding document for public teachers, only encourages its use according to the purpose of the learning session. In 2020, the Closing Digital Divide strategy revealed that 81% of public teachers required training to integrate technologies into their pedagogical practice. This study used structural analysis to analyse key factors in teachers’ training to improve their digital competence. Results showed that among the key factors of the training system were the differentiated accompaniment in the use of ICT, the courses based on the participants’ profile, the blended learning model, the technological infrastructure within the institutions and the creation of digital competence within the Framework of Teaching Performance. The results provide support to provide guidance to create the required digital training for teachers. Future research should evaluate digital teacher training policies, as well as the role of the school leaders in the implementation of ICT.